Transition scenario in hypersonic axisymmetrical compression ramp flow. (17th November 2020) - Lugrin, Mathieu; Beneddine, Samir; Leclercq, Colin; Garnier, Eric; Bur, Reynald
Abstract: Abstract : A high-fidelity simulation of the shock/transitional boundary layer interaction caused by a $15^°$ axisymmetrical compression ramp is performed at a free stream Mach number of 5 and a transitional Reynolds number. The inlet of the computational domain is perturbed with a white noise in order to excite convective instabilities. Coherent structures are extracted using spectral proper orthogonal decomposition (SPOD), which gives a mathematically optimal decomposition of spatio-temporally correlated structures within the flow. The mean flow is used to perform a resolvent analysis in order to study non-normal linear amplification mechanisms. The comparison between the resolvent analysis and the SPOD results provides insight on both the linear and nonlinear mechanisms at play in the flow. To carry out the analysis, the flow is separated into three main regions of interest: the attached boundary layer, the mixing layer and the reattachment region. The observed transition process is dependent on the linear amplification of oblique modes in the boundary layer over a broad range of frequencies. These modes interact nonlinearly to create elongated streamwise structures which are then amplified by a linear mechanism in the rest of the domain until they break down in the reattachment region. The early nonlinear interaction is found to be essential for the transition process.